Enhanced inhibitory synaptic transmission in the spinal dorsal horn mediates antinociceptive effects of TC-2559 - Peng Li-Chao; Huang Lan-Ting; Fan Jing; Han Lei; Cheng Long-Zhen; Wang Yun (SAGE Publishing, 2011)
Abstract Background TC-2559 is a selective α4β2 subtype of nicotinic acetylcholine receptor (nAChR) partial agonist and α4β2 nAChR activation has been related to antinociception. The aim of this study is to investigate the analgesic effect of TC-2559 and its underlying spinal mechanisms. Results 1) In vivo bioavailability study: TC-2559 (3 mg/kg) had high absorption rate in rats with maximal total brain concentration reached over 4.6 μM within first 15 min after administration and eliminated rapidly with brain half life of about 20 min after injection. 2) In vivo behavioral experiments: TC-2559 exerts dose dependent antinociceptive effects in both formalin test in mice and chronic constriction injury (CCI) model in rats by activation of α4β2 nAChRs; 3) Whole-cell patch-clamp studies in the superficial dorsal horn neurons of the spinal cord slices: perfusion of TC-2559 (2 μM) significantly increased the frequency, but not amplitude of spontaneous inhibitory postsynaptic currents (sIPSCs). The enhancement of sIPSCs was blocked by pre-application of DHβE (2 μM), a selective α4β2 nicotinic receptor antagonist. Neither the frequency nor the amplitude of spontaneous excitatory postsynaptic currents (sEPSCs) of spinal dorsal horn neurons were affected by TC-2559. Conclusions Enhancement of inhibitory synaptic transmission in the spinal dorsal horn via activation of α4β2 nAChRs may be one of the mechanisms of the antinociceptive effects of TC-2559 on pathological pain models. It provides further evidence to support the notion that selective α4β2 subtype nAChR agonist may be developed as new analgesic drug for the treatment of neuropathic pain.